2009
DOI: 10.1007/s10495-008-0297-3
|View full text |Cite
|
Sign up to set email alerts
|

Pan-caspase inhibition suppresses polyethylene particle-induced osteolysis

Abstract: Particle-induced osteolysis is a major cause of aseptic loosening after total joint replacement. Earlier studies demonstrated apoptotic macrophages, giant cells, fibroblasts and T-lymphocytes in capsules and interface membranes of patients with aseptic hip implant loosening. The aim of the current study was to determine in a murine calvarial model of wear particle-induced osteolysis whether inhibition of apoptosis using the pan-caspase inhibitor BOC-D-FMK reduces aseptic loosening. Healthy 12-week-old male C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…It is known that LPS can be present in periprosthetic tissue of patients with loosened implants but in whom there is no clinical or microbiological evidence of infection 36 . Endotoxin contamination of orthopedic implants and wear debris is common and appears to be an important component of biological activity 37 . In our study, there was no bacteriological evidence of infection, suggesting that this can be considered a model of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that LPS can be present in periprosthetic tissue of patients with loosened implants but in whom there is no clinical or microbiological evidence of infection 36 . Endotoxin contamination of orthopedic implants and wear debris is common and appears to be an important component of biological activity 37 . In our study, there was no bacteriological evidence of infection, suggesting that this can be considered a model of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…This in vitro evidence has been supported by in vivo immunohistochemistry of central apoptosis-related mediators such as caspase-3 associated with macrophages, giant cells, and T-lymphocytes in local tissues (capsules and interfacial membranes) of patients with aseptic hip implants [55, 56]. The importance of apoptosis associated mediators has been made clear by murine osteolysis models that demonstrated inhibition of apoptosis by a pan-caspase inhibitor leads to decreasing bone resorption by osteoclasts [57] and presumably decreased amounts of apoptosis associated cytokines like interleukin-8 (IL-8), monocyte chemoattractant protein-1 (MCP-1), intercellular adhesion molecule-1, and type-1 interferon [58, 59]. …”
Section: Initial Mechanisms For the Wear Particle Related Activatimentioning
confidence: 98%
“…The induction of apoptosis-like responses associated with implant debris has also been correlated with implant debris in vivo , such as caspase-3 associated with macrophages, giant cells, and T-lymphocytes in local tissues (capsules and interfacial membranes) of patients with aseptic hip implants (59). But, it is important not to confuse apoptosis with that of danger signaling and other inflammatory pathways because early studies using pan-caspase inhibitors (which inhibit danger signaling) erroneously concluded that inhibition of apoptosis by a pan-caspase inhibitors mitigates implant-induced inflammation osteolysis (60), when in fact it was the pan-caspase inhibition of inflammation pathways that decreased inflammation (8, 11). The role of apoptosis, pyroptosis, and pyronecrosis in implant-induced inflammation is still unclear and controversial.…”
Section: Adaptive Immune Responsesmentioning
confidence: 99%